Outcomes of the short Synacthen test: what is the role of the 60 min sample in clinical practice?. Issue 1132 (25th September 2019) - Dineen, Rosemary; Mohamed, Ahmed; Gunness, Anjuli; Rakovac, Ana; Cullen, Emer; Barnwell, Niamh; Neary, Catherine; Behan, Lucy-Ann; Boran, Gerard; Gibney, James; Sherlock, Mark
Abstract: : In recent years, the short Synacthen test (SS) has become the most widely used test to assess adrenal reserve. Despite its frequent use, there are still several areas related to the short Synacthen test (SST), which have no consensus including the optimum sampling times, that is, whether a 60 min post-Synacthen administration cortisol is necessary or not. Methodology: We performed a retrospective data analysis of 492 SSTs performed on adult patients in a tertiary referral teaching hospital in Ireland. The SSTs were performed in the inpatient and outpatient setting and included patients across all medical disciplines and not exclusively to the endocrinology department. Results: 313 patients had 0, 30 and 60 min samples available for analysis. A total of 270/313 (82%) were deemed to pass the test, that is, cortisol ≥500 nmol/L at both 30 and 60 min. Of the 313 patients, 19 (6%) patients had an indeterminate response, cortisol <500 nmol/L at 30 min, but rising to ≥500 nmol/L on the 60 min sample. Of these 19 patients, only 9/19 patients had a serum cortisol level at 30 min <450 nmol/L, requiring clinical treatment with glucocorticoid replacement. All 24/313 (8%) patients who had insufficient responses at 60 min were also insufficient at 30 min sampling. No individuals passed (≥500 nmol/L) at 30 min and then failed (<500 nmol/L) at 60 min. Conclusion: Using the 30 min cortisol sample post-Synacthen administration alone identifies clinically relevant adrenal insufficiency in the majority of cases. A small subset of patients have a suboptimal response at 30 min but have a 60 min cortisol concentration above the threshold for a pass. Data regarding the long-term outcomes and management of such patients are lacking and require further study.